Comparison of moisture buffering properties of plasters in full scale simulations and laboratory testing. (20th August 2020) - Cascione, Valeria; Maskell, Daniel; Shea, Andy; Walker, Pete; Mani, Monto
Highlights: MB tests do not give quantitative information on materials' behaviour in buildings. Simulations help understanding moisture buffering impact of materials in buildings. Plasters reduce humidity peaks due to sorption capacity and vapour permeability. Plasters' moisture buffeting capacity is smaller in simulations than in laboratory testing. Ventilation and moisture transport through the enclosure influence materials' MBV. Abstract: The regulation of indoor relative humidity is a key factor for the provision of occupant health and comfort. Passive humidity regulation is possible if porous materials, for example clay and gypsum plasters, are exposed to the indoor environment. Materials that are highly hygroscopic can help regulate relative humidity levels through their capacity to adsorb and release water vapour from and to the indoor air via a dynamic process referred to as moisture buffering. Laboratory test methods have been developed to measure this moisture buffering capacity, which are well-suited for comparative testing of relatively small material samples under controlled conditions. However, quantification of the impact of hygroscopic materials in real buildings requires additional evaluation, like field testing and the support of simulation models, which can successively be used for the development of new protocols capable of giving information about materials' moisture buffering performances indoors. This paper investigates moisture buffering capacity of three hygroscopic plasters (clay, gypsum and lime), and compares measurements obtained in the laboratory to those from numerical simulations of a single-zone room space. The dynamic sorption capacity of the plasters was investigated using the NORDTEST protocol and results compared to those from hygrothermal simulation. Differences are identified between the two methods in the quantification of the moisture buffering potential, which lead to further investigation on the effect of ventilation and moisture transport through the entire wall assembly. The significance of this paper is to show building moisture regulation involves also different factors, such as ventilation and walls moisture transport, which will impact the moisture buffering potentials indoors. Consequently, it is necessary to better understand moisture buffering in real buildings, to quantify the influence of hygroscopic materials indoors, and introduce alternative laboratory testing, to give quantitative information about their impact in buildings.